Alloiothucha artocarpi (Horváth) (Hemiptera: Heteroptera: Tingidae) found on jackfruit, Artocarpus heterophyllus Lam. (Moraceae): first representative of the genus from Laos, and the synonymy of Cetiothucha Drake & Ruhoff - Souma, Jun; Cho, Geonho; Lee, Seunghwan (Zootaxa, 2022)
The lace bug genus Alloiothucha Drake, 1927 (Hemiptera: Heteroptera: Tingidae) is recorded from Laos for the first time with the redescription of Alloiothucha artocarpi (Horváth, 1926), which has been originally described from Indonesia (Java Island) in Latin. This species was collected on jackfruit, Artocarpus heterophyllus Lam. (Moraceae) in Laos, and may represent a pest of potential future concern. An identification key to all described species of Alloiothucha and arguments for a junior synonymy of Cetiothucha is presented: Alloiothucha Drake, 1927 = Cetiothucha Drake & Ruhoff, 1965, syn. nov. Two new combinations are proposed: Alloiothucha constanti (Guilbert, Pham & Soulier-Perkins, 2018), comb. nov. and Alloiothucha physalia (Drake & Ruhoff, 1965), comb. nov. from Cetiothucha.